Redistributive Taxation in Dynamic General Equilibrium with Heterogeneous Agents - Putz, Christian (Schriften aus der Fakultät Sozial- und Wirtschaftswissenschaften der Otto-Friedrich-Universität Bamberg, 2020)
The consideration of the distribution of income, wealth and consumption within countries around the globe reveals one basic and consistent picture: inequality in the allocation of resources is a prevailing global phenomenon and subject to an ongoing negative trend since, at least, the last three decades. In general, governments are equipped with a range of instruments and tools to influence distribution, with redistributive tax systems being considered the most direct, powerful and popular instrument in this context. Besides its influence on resource allocation, however, tax and transfer policies also possess substantial effects on many economic areas, for example, economic growth, financial markets and individual as well as aggregate welfare. Although widely discussed, the effects of taxation and redistribution as well as the underlying causes are not yet fully understood. By the means of economic equilibrium models the present work, therefore, addresses the influence of redistributive taxation within a closed economy populated by heterogeneous agents. The results show that rising tax rates on labor income or capital gains are generally associated with decreasing economic growth rates and, hence, diminishing future consumption possibilities. Moreover, in a variety of cases, redistributive taxation might foster inequality in wealth, consumption and participation rates. Even when effective, redistributive taxation is generally associated with a trade-off between macroeconomic growth and equality (or welfare).